Health Risk Assessment of Occupational Exposure to BTEX in the Painting unit of a Bicycle Industry in Quchan, Iran - Mahmoud Mohammadyan; Hadi Naderi; Seyed Nouraddin Mousavinasab; Hadi Mahmoodi sharafe; Ali Rafiei; Mohammad Dasturani (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Benzene, Toluene, Ethylbenzene, and Xylenes (BTEX) is regarded as one of the most important pollutants in organic compounds present in paint compounds the toxic effects of which are well known. Therefore, the aim of this study was to investigate the health risk assessment of exposure of the painting unit workers of a bicycle industry to BTEX compounds and provide control solutions. Methods: In this cross-sectional study, 48 personal exposure samples of workers during two seasons of winter and spring were collected using the National Institute for Occupational Safety and Health 1501 (NIOSH 1501) method from six sections of the painting unit in a bicycle industry. Then, the data were analyzed by Gas Chromatography with Flame Ionization Detector (GC-FID) and their exposure risk was estimated by the Environmental Protection Agency (EPA) method. Results: The cancer risk of benzene and ethylbenzene in all sections exceeded the EPA acceptable criteria. The paint preparation cabin had the highest cancer risk with 8.2 per 1,000 and 1.2 per 1,000 workers for benzene and ethylbenzene, respectively. Noncancer risk of benzene in all sections, toluene in the primer paint cabin and polishing and finishing paint cabin, and xylene in the paint preparation cabin and cascade painting exceeded the EPA criteria. Conclusion:  Due to the high levels of cancer risk of benzene and ethylbenzene in all sections, high noncancer risk of BTEX compounds in some sections, and in general simultaneous presence of all vapors of BTEX, all sections of paint unit need to be improved in terms of the working environment, such as engineering controls and modification of work procedures.